APAKAH SHISHA BERBAHAYA BAGI KESEHATAN RONGGA MULUT ? - Andi Anggun Mauliana Putri; Gus Permana Subita (Odonto : Dental Journal, 2017)
Background: In recent years, the use of tobacco in Indonesia increasingly varied in the forms and methods of consumption, one of which is shisha. Smoking shisha is increasingly popular due to a misperception that smoking shisha is harmless and lack of knowledge about the eﬀects of shisha smoking in oral health.Literature analysis: “PubMed” used as a search tool to identify all empirical studies related to the eﬀects of shisha smoking on health, especially in oral cavity.Discussion: Shisha smoke contained various toxic substances such as Nicotine, Tobacco Specifc Nitrosamines, Polycyclic Aromatic Hydrocarbons, Volatile Organic Compounds, Carbon Monoxide, Tar, and high-temperature metal heating causing shisha smoke contained toxic heavy metals such as arsenic, nickel, cobalt, chromium, lead, and cadmium. The content of these toxic substances showed that smoked shisha is associated with dependence, acute and long-term negative health eﬀects similar to cigarette smoking. Toxic substances may cause various infections of microorganism such as Candida sp, Herpes Simplex Virus (HSV-1), Epstein Barr Virus, Mycobacterium tuberculosis, Human Immunodefciency Virus; Oral mucosal changes such as Hairy Tongue, Smoker’s Melanosis, Nicotine Stomatitis, Frictional Keratosis, Fissured Tongues, gingival or periodontal inﬂammation, and leukodema; and lead to malignant lesions such as Keratosis, Leukoplakia, Erythroplakia, Oral Submucous Fibrosis and Lichenoid Lesions.Conclusion: Smoking shisha gives bad impact for human health especiallyoral health. Shisha smoking can lead to the development of various infectious diseases and potentially lead to malignancy in the oral mucosa. These foundings breaks the belief that shisha smoking is safe for health.